2017
DOI: 10.5812/ijp.58924
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Diagnosis, Biochemical Findings, Genetics and Incidence of Zellweger Syndrome

Abstract: Objectives: To analyze the clinical and laboratory data of neonates diagnosed with Zellweger syndrome and to estimate the incidence of the syndrome. Methods: The databases of four institutions that admitted newborns diagnosed with Zellweger syndrome to intensive care units between January 2013 and December 2016 were examined. Results: A total of 105,887 live babies were born in the four centers during the study period. Seven were diagnosed with Zellweger syndrome; the incidence was thus 1/15,126. Birth weights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…Affected individuals with ZSD manifest with severe neurological impairment, respiratory muscle weakness, and airway aspirations. Celik et al reported seven infants with Zellweger disease who were admitted to neonatal intensive care unit with respiratory distress, hypotonia, and/or convulsions . Both of our patients with Zellweger syndrome also presented with similar respiratory manifestations.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Affected individuals with ZSD manifest with severe neurological impairment, respiratory muscle weakness, and airway aspirations. Celik et al reported seven infants with Zellweger disease who were admitted to neonatal intensive care unit with respiratory distress, hypotonia, and/or convulsions . Both of our patients with Zellweger syndrome also presented with similar respiratory manifestations.…”
Section: Discussionsupporting
confidence: 61%
“…30 Galactosialidosis is a LSD characterized by fetal hydrops, congenital heart defects, hepatosplenomegaly, complex neurological impairment, and skeletal abnormalities. 31 34 Both of our patients with Zellweger syndrome also presented with similar respiratory manifestations.…”
Section: Discussionmentioning
confidence: 52%
“…EIMEE is an umbrella term for many channelopathies and IEM, such as D-glyceric acidemia, propionic aciduria, molybdenum cofactor deficiency, pyridoxine deficiency, methylmalonic acidemia, sulfite oxidase deficiency, Menkes disease, and Zellweger syndrome. Within this group of channelopathies, we found the following [50][51][52][53][54][55][56].…”
Section: Dee Presents With Predominant Myoclonic Seizuresmentioning
confidence: 81%